A risk‐based postresection follow‐up strategy for hepatocellular carcinoma patients. Issue 4 (20th December 2022) - Fu, Yizhen; Li, Xia; Yang, Zhenyun; Li, Shaoqiang; Pan, Yangxun; Chen, Jinbin; Wang, Juncheng; Hu, Dandan; Zhou, Zhongguo; Xu, Li; Chen, Minshan; Zhang, Yaojun
Abstract: Background: The optimal intervals for follow‐up after hepatocellular carcinoma (HCC) patients undergo curative liver resection (LR) remain unclear. This study aimed to establish a risk‐based post‐resection follow‐up strategy. Methods: Patients that were diagnosed with HCC and received LR from three hospitals in China were included. The risk‐based strategy was established based on the random survival forest model and compared with a fixed strategy both internally and externally. Results: In total, 3447 patients from three hospitals were included. The authors' strategy showed superiority in the early detection of tumor relapse compared with fixed surveillance. Under fewer total visits, risk‐based strategy achieved analogous survival time compared to the total 20 times follow‐ups based on fixed strategy. Twelve total visits (five, three, one, two, and one visits in years 1–5, respectively) for American Joint Committee on Cancer/International Union Against Cancer T1a stage patients, 13 total visits (five, four, one, two, and one visits in years 1–5, respectively) for T1b stage patients, 15 total visits (eight, three, three, zero, and one visits in years 1–5, respectively) for T2 stage patients, and 15 total visits (eight, four, one, one, and one visits in years 1–5, respectively) for T3 stage patients were advocated. The detailed follow‐up arrangements were available to the public through an interactive website (https://sysuccfyz.shinyapps.io/RiskBasedFollowUp/ ). Conclusion: This risk‐based surveillance strategy was demonstrated to detect relapse earlier and reduce the total number of follow‐ups without compromising on survival. Based on the strategy and methodology of the authors, surgeons or patients could choose more intensive or flexible schedules depending on the requirements and economic conditions. Plain language summary: A risk‐based post‐resection follow‐up strategy was established by random survival forest model using a larger hepatocellular carcinoma population The strategy was demonstrated to detect tumor relapse earlier and reduce the total number of follow‐ups without compromising on survival Our strategy and methodology could be widely applied by other surgeons and patients Abstract : A risk‐based postresection follow‐up strategy was established by random survival forest model using a larger hepatocellular carcinoma population. The strategy was demonstrated to detect tumor relapse earlier and reduce the total number of follow‐ups without compromising on survival.